The effect of spiritual counseling in the rehabilitation and correction of offenders - Ngwana, Rudzani Gabriel (University of Limpopo (Turfloop Campus), 2011)
Refer to document
Thesis (M.A. (Philosophy)) --University of Limpopo, 2011
Keywords: Spiritual counselling; Rehabilitation; Offenders; 364.48; Couselling; Crime prevention; Rehabilitation